Analysis of Learning Needs for Writing Negotiation Texts Using the RAFT Strategy Among 10th-Grade Vocational High School Students - Fitri Febrianty; Setyawan Pujiono (Journal of Educational Sciences, 2026)
This study aims to analyze the learning needs for writing negotiation texts using the RAFT (Role, Audience, Format, Topic) strategy for 10th-grade students at SMK YPC Tasikmalaya. The study employs a qualitative descriptive design based on a needs analysis framework for 10th-grade students at SMK YPC Tasikmalaya. This study employs a qualitative descriptive approach based on a needs analysis framework. Data were collected through classroom observations, in-depth interviews, and questionnaires involving one Indonesian language teacher and 30 10th-grade students at SMK YPC Tasikmalaya. Data were analyzed using the interactive analysis model by Miles, Huberman, and Saldana (2014). The results of the study indicate that: (1) students’ ability to write negotiation texts remains low, characterized by difficulties in structuring the text, selecting persuasive vocabulary, and constructing logical arguments; (2) the teaching of negotiation text writing remains conventional, thus failing to encourage student engagement and creativity; (3) the RAFT strategy has great potential for application because the components of Role, Audience, Format, and Topic align with the characteristics of negotiation texts. The results of this needs analysis can be used as a basis for developing a RAFT-based negotiation text writing learning module to improve the communicative and persuasive thinking skills of vocational high school students.